Western Anti-Communism and the Interdoc Network - Scott-Smith, Giles. author. aut Link
XVI, 388 p.
Keywords: Interdoc was established in 1963 by Western intelligence services as a multinational effort to coordinate an anti-communist offensive. Drawing on exclusive sources and the memories of its participants, this book charts Interdoc's campaign, the people and ideas that lay behind it and the rise and fall of this remarkable network during the Cold War.